"Dios, qué buen vassalo, si oviesse buen señor!" : as relações de negociação e poder monárquico em Castela no século XIII à luz do Poema de Mio Cid (1207) - Couto, Lívia Maria Albuquerque (2019)
The reign of Alfonso VIII (1158-1214) was a period marked by a series of political and military conflicts. In order to understand this period of Castilian history and to contribute to what is researched about the Iberian Middle Ages, we seek to analyze the relationship of this monarch with a specific part of society, that is, the warrior / seigneurial aristocracy. To do so, we will use the poem of Mio Cid, written during the reign of Alfonso VIII, which will allow us to analyze how the discourse on seigneurial negotiations and monarchic power were represented in the Castilian court. Thus we hope to understand not only the idealized aristocratic model, but also the negotiation relationships sought by the monarchy. In this sense, we highlight how Alfonso VIII used court literature in order to improve tensions with the aristocracy and to help legitimize its power. In attributing propagandist characteristics as, for example: Balance, Loyalty, Courtesy, Religious Generosity and the ideal of Hero / Warrior, the Castilian monarch sought to shape social reality in his favor. Therefore, we believe that in order to attribute negotiation discourses based on these characteristics and to strengthen their monarchical power specific situations in the Poem of Mio Cid were used. It is therefore necessary to think of the poetic content of the document within a context, relating its discourse to the specific social and power relations of Castile in the13th century. It is necessary to emphasize that the document was produced between the two main wars of the reign of Alfonso VIII (Alarcos and Las Navas). Finally, we believe in the idea that Alfonso VIII used the literary production of the time, that is, the poem of Mio Cid as a propagandistic instrument to serve as a model of social relations and negotiation between the Castilian monarchy and the aristocracy.